Continuous assessment for learning: issues of multiple instances of peer feedback in a university course - Mottier Lopez, Lucie; Girardet, Céline; Naji, Taha (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2021)
In the context of continuous assessment for learning in a university course in French-speaking Switzerland, this article studies students’ perception when they receive multiple instances of peer feedback on a written academic assignment carried out in small collaborative groups. How do students, who are both assessees and assessors, perceive these multiple instances of feedback, especially when they are led to compare them to regulate their own initial work and their assessment skills? This article analyses in detail the processes and feelings at play when students notice similarities and differences between the instances of feedback they received and produced. Conceptual considerations are proposed around the notions of feedback, internal feedback, comprehensive feedback, and metafeedback, seen as contributing to the regulation and learning processes involved.